The predictors of healthcare utilization and analyzing equity level in healthcare utilization in Turkey - ÇELİK, YUSUF (My University, 2022)
This study aims to analyse and evaluate the equity level of healthcare utilization by years in Türkiye by exploring the relationship between health services utilization and the factors that are predisposing, enabling and need factors in \"Behavioural Model\" developed by Andersen.Material and Methods:The concentration index and regression analyses were used to estimate equity levels and to explore the effects of predisposing, enabling and need factors. Data of 5 Türkiye Health Surveys conducted in years of 2008, 2010, 2012, 2014 and 2016 was used to reach this study\"s purposes. Equity in healthcare utilization was investigated for four healthcare utilization indicators: 1) Services provided by family/practitioner physicians, 2) Services provided by specialized physicians, 3) Day care/outpatient care services, and 4) Inpatient care services provided by hospitals.Results:Estimated concentration index values for income level, education level, and number of diseases showed that health services utilization was concentrated among people having less income and education level as well as more diseases. Regression analyses also indicated that the variables of income and education level, and disease existence and number of diseases as well as some other socio-demographic characteristics of individuals had significant effects on health services utilization.Conclusion:Considering the effects of predisposing, enabling and need factors on the utilization of health services in Türkiye by years, it might be concluded that equity level in Turkish Healthcare System has been improved.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)